1981
DOI: 10.1017/s0021859600036017
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sowing Date on the Yield and Yield Components of Spring Oil-Seed Rape

Abstract: SUMMARYThree spring oil-seed rape cultivars were drilled on five dates during 1979 and 1980. Delayed drilling (1) reduced seed yield, (2) increased the main stem contribution to seed production, and (3) increased the percentage of damaged pods at harvest. The results indicated that cultivars similar to those used in this trial should be drilled between the 3rd week of March and mid-April.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…S1 ). Earlier studies also implied a lower relevance of TSW for seed yield compared with the effect of the number of seeds per silique and the number of siliques per plant ( Scarisbrick et al , 1981 ; Diepenbrock, 2000 ; Berry and Spink, 2009 ; Chen et al , 2014 ; Labra et al , 2017 ). We also found no decrease of TSW associated with increasing N fertilization, although such an effect had been observed in a single environment in an older study on spring-type oilseed rape ( Hocking et al , 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). Earlier studies also implied a lower relevance of TSW for seed yield compared with the effect of the number of seeds per silique and the number of siliques per plant ( Scarisbrick et al , 1981 ; Diepenbrock, 2000 ; Berry and Spink, 2009 ; Chen et al , 2014 ; Labra et al , 2017 ). We also found no decrease of TSW associated with increasing N fertilization, although such an effect had been observed in a single environment in an older study on spring-type oilseed rape ( Hocking et al , 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that winter and spring varieties of oil-seed rape are especially sensitive to sowing date. For example when three spring varieties were drilled on five dates (from 20 March until 9 May) mean seed yields declined from 1-22 to 0-41 t/ha and from 1-55 to 0-22 t/ha in 1979 and 1980 respectively (Scarisbrick, Daniels & Alcock, 1981). Similarly when the sowing date of winter oil-seed rape was staggered from early September to mid-October, yield was reduced by 30 % in Agricultural Development and Advisory Service trials (Mac-Leod, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results do indicate that, (i) size (3-12 plants) used in most published studies, for example Ogunremi (1970); Scarisbrick et al (1981), was probably too small to compare treatment means reliably, and (ii) that plant dry weight data obtained from smaller quadrat areas taken from a range of plot sites may be used to estimate number of pods. A linear regression analysis on all data of number of pods and plant weight demonstrated that number of pods per plant = 4-3 x plant dry weight, the regression coefficient having a standard error of +0-1.…”
Section: Meansmentioning
confidence: 83%
“…The response of three spring cultivars of oilseed rape to five levels of nitrogen fertilizer (0 to 200 kg/ha) was studied during 1978-9 (Scarisbrick, Daniels & Alcock, 1981). Sampling problems, practical difficulties of measuring yield components, and the high co-efficients of variation for these data were discussed.…”
mentioning
confidence: 99%